2014
DOI: 10.1371/journal.pone.0088108
|View full text |Cite
|
Sign up to set email alerts
|

“Limits of Control” – Crucial Parameters for a Reliable Quantification of Viable Campylobacter by Real-Time PCR

Abstract: The unsuitability of the “CFU” parameter and the usefulness of cultivation-independent quantification of Campylobacter on chicken products, reflecting the actual risk for infection, is increasingly becoming obvious. Recently, real-time PCR methods in combination with the use of DNA intercalators, which block DNA amplification from dead bacteria, have seen wide application. However, much confusion exists in the correct interpretation of such assays. Campylobacter is confronted by oxidative and cold stress outsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 23 publications
5
49
1
Order By: Relevance
“…PMA does not readily penetrate the membrane of living cells, and it mainly relies on free diffusion to reach the DNA of cells with compromised membranes (Nocker et al, 2006). For live cells with intact membranes, previous studies suggested that cell uptake might explain the reduction in DNA detection (Nkuipou-Kenfack et al, 2013;Kruger et al, 2014). These two different principles result in different efficiencies with these two types of cell.…”
Section: Discussionmentioning
confidence: 99%
“…PMA does not readily penetrate the membrane of living cells, and it mainly relies on free diffusion to reach the DNA of cells with compromised membranes (Nocker et al, 2006). For live cells with intact membranes, previous studies suggested that cell uptake might explain the reduction in DNA detection (Nkuipou-Kenfack et al, 2013;Kruger et al, 2014). These two different principles result in different efficiencies with these two types of cell.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the optimized quantity of PMA might be a critical limiting factor if the optimization is made using a pure culture. Kruger et al (2014) suggested that in broiler carcass rinse the composition of the matrix severely affected PMA dead signal reduction. According to van Frankenhuyzen et al (2011) the turbidity of the sample can also pose a problem if optimization doesn't occur first.…”
Section: Discussionmentioning
confidence: 99%
“…Since cell membrane integrity is essential for bacteria viability, the dyes that are used to block the DNA originating from dead cells and their application to molecular methods have a huge potential. According to Kruger et al (2014) detecting cells that own an intact membrane, which is non-permeable to the widely accepted live/dead discriminatory DNA dye, would be more suitable to reflect the potential risk for infection by food products, in particular when the bacteria are stressed and lose their ability to grow on plates. For Dinu and Bach (2013) a high correlation between the PMA-qPCR results and the total viable counts detected by the fluorescence microscopy of Escherichia coli could be established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this approach can overestimate the number of viable cells due to the presence of free extracellular DNA (eDNA) (Klein et al, 2012) and DNA derived from dead cells. To avoid quantification of DNA not derived from living cells, samples can be treated with propidium monoazide (PMA) prior to DNA extraction (Alvarez et al, 2013;Kruger et al, 2014;Yasunaga et al, 2013). This molecule enters only membrane-compromised cells, intercalating between bases, and also interacts with eDNA (Nocker et al, 2007;Waring, 1965).…”
Section: Microbiological and Molecular Methodsmentioning
confidence: 99%